Analisa Penyusunan Strategi Marketing Mix Sebagai Alternatif Promosi Rumah Sakit Di RSUD Simpang Lima Gumul Kediri - Dwi Laksana, Ema; Dian E, Agusta; Pilatusalim, Melany; Ismurdijahmitra , Mimiet (Jurnal Syntax Fusion, 2022)
The RSUD Simpang Lima Gumul is a complete health service unit for all levels of society that is oriented to quality and patient safety in Kediri Regency. A preliminary study obtained from 20 respondents stated that the community was still not familiar with the Simpang Lima Gumul Kediri Hospital, because the service facilities were still relatively new. Therefore, the marketing mix strategy can be an alternative health promotion for Simpang Lima Gumul Hospital. This residency was conducted to identify the factors to determine the marketing mix strategy as an alternative to health promotion. This residency was carried out in June 2022 at the Simpang Lima Gumul Hospital using USG and SWOT analysis, then an evaluation was carried out. The results of the residency show that there is no SOP on marketing regarding health promotion. The conclusion of this residency is the need to make marketing about hospital promotions at Simpang Lima Gumul Kediri Hospital and evaluate its implementation regularly.